Forced to go virtual? Distributed cooperation of small software firms. (1st July 2013) - ,; ,; ,; ,
Abstract : Within the service sector, the software industry has been among the prime movers in the process of offshoring work to new destinations. This is facilitated by the immaterial character of the products and their components and by the industry's inclination to use new technical opportunities for its own purposes as well. This paper investigates practices of virtual cooperation and team work in small and start-up software companies based in Austria. Evidence indicates that because of their niche strategies and the related conditions of their national context, these companies often depend on international cooperation which, in turn, often takes on a 'virtual' form.